2023
DOI: 10.1007/s12519-023-00738-2
|View full text |Cite
|
Sign up to set email alerts
|

Delivery room resuscitation intensity and associated neonatal outcomes of 24+0–31+6 weeks’ preterm infants in China: a retrospective cross-sectional study

Abstract: Background The aim of this study was to review current delivery room (DR) resuscitation intensity in Chinese tertiary neonatal intensive care units and to investigate the association between DR resuscitation intensity and short-term outcomes in preterm infants born at 24+0–31+6 weeks’ gestation age (GA). Methods This was a retrospective cross-sectional study. The source population was infants born at 24+0–31+6 weeks’ GA who were enrolled in the Chinese Neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Neonatal resuscitation almost always predicts an inability to establish spontaneous breathing, 11 and the correct implementation of neonatal resuscitation techniques can establish effective ventilation for the neonate and help him or her make a successful transition from the intrauterine to the extrauterine environment. Although guidelines for neonatal resuscitation have been updated, in China, resuscitation strategies vary widely between centres 20 and the practice and management of neonatal resuscitation are not standardised in each region. Moreover, there are very few follow-up studies on neonatal resuscitation, and the prognosis of resuscitated neonates remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal resuscitation almost always predicts an inability to establish spontaneous breathing, 11 and the correct implementation of neonatal resuscitation techniques can establish effective ventilation for the neonate and help him or her make a successful transition from the intrauterine to the extrauterine environment. Although guidelines for neonatal resuscitation have been updated, in China, resuscitation strategies vary widely between centres 20 and the practice and management of neonatal resuscitation are not standardised in each region. Moreover, there are very few follow-up studies on neonatal resuscitation, and the prognosis of resuscitated neonates remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study reported the short-term outcomes of delivery room resuscitation for very preterm and very low birth weight infants in 33 neonatal intensive care units (NICUs) in five provinces and cities in North China, although it did not provide information regarding post-discharge follow-up and outcomes of the infants. 18 Another retrospective study published in 2021 reported the clinical features of preterm infants with a birth weight of <1500 g who received resuscitation of different intensities in NICUs of 20 hospitals in Jiangsu province, 19 while yet another retrospective study published in 2023 reported the correlation between the intensity of delivery room resuscitation of preterm infants with a gestational age (GA) of 24 +0 –31 +6 weeks and their short-term outcomes from the Chinese Neonatal Network 20 ; however, both these studies provided incomplete information for some cases.…”
Section: Introductionmentioning
confidence: 99%